Neuropilin-1 Identifies a New Subpopulation of TGF-β-Induced Foxp3+ Regulatory T Cells With Potent Suppressive Function and Enhanced Stability During Inflammation - Chen, Weiqian; Huang, Weishan; Xue, Youqiu; Chen, Ye; Qian, Wenbin; Ma, Jilin; August, Avery; Wang, Julie; Zheng, Song Guo; Lin, Jin (Frontiers in Immunology, 2022)
CD4+Foxp3+ regulatory T cells (Tregs) play a crucial role in preventing autoimmunity and inflammation. There are naturally-derived in the thymus (tTreg), generated extrathymically in the periphery (pTreg), and induced in vitro culture (iTreg) with different characteristics of suppressiveness, stability, and plasticity. There is an abundance of published data on neuropilin-1 (Nrp-1) as a tTreg marker, but little data exist on iTreg. The fidelity of Nrp-1 as a tTreg marker and its role in iTreg remains to be explored. This study found that Nrp-1 was expressed by a subset of Foxp3+CD4+T cells in the central and peripheral lymphoid organs in intact mice, as well as in iTreg. Nrp-1+iTreg and Nrp-1-iTreg were adoptively transferred into a T cell-mediated colitis model to determine their ability to suppress inflammation. Differences in gene expression between Nrp-1+ and Nrp-1-iTreg were analyzed by RNA sequencing. We demonstrated that the Nrp-1+ subset of the iTreg exhibited enhanced suppressive function and stability compared to the Nrp-1- counterpart both in vivo and in vitro, partly depending on IL-10. We found that Nrp-1 is not an exclusive marker of tTreg, however, it is a biomarker identifying a new subset of iTreg with enhanced suppressive function, implicating a potential for Nrp-1+iTreg cell therapy for autoimmune and inflammatory diseases.